Impaired Metabolism Induced By Perinatal Hypoxia - Elizabeta, Zisovska; Kornelija, Trajkova (International Journal of Innovative Research in Medical Science, 2016)
Perinatal hypoxia induces disturbances in glucose metabolism. In anaerobic environment, high level of lactate production persists, causing endothelial damage and deleterious effect on the brain. The outcome depends on the brain capacity to utilize lactate and ketones as an alternative energy source to glucose. There isn't evidence that depriving infants of glucose after hypoxia is neuroprotective. The aim of our study was to present the results of blood investigation for blood sugar level (BSL), lactate level (LL), and to assess the correlation between these markers and severity of Hypoxic-ischemic encephalopathy (HIE). Material: asphyxiated newborns born at Obstetric&Gynecology Clinic in Macedonia. Methods: clinical, biochemical, statistical. Results: at first sight we got almost normal value of BSL (mean value in healthy full-term infants was 2,8 mmol/l, in examined group 2,7 mmol/l), but deep analysis of distribution showed three-modal curve: 33% of them had normal value (3,1 mmol/l), 43% of the babies were hypoglycemic (BSL 1,3 mmol/l) and 24% were hyperglycemic with BSL of 4,8 mmol/l. The LL had very concordant distribution: in hypoglycemic infants LL was much lower than normal values (<0,9 micromol/l compared to normal value 1,2-1,8 micromol/l), similar in normoglycemic infants (LL was 1,0 micromol/l), in hyperglycemic the LL increased significantly to 2,8 micromol/l,. The Spearman coefficient of correlation showed moderate level of correlation between LL and severity of HIE (r=0,65). Conclusion: perinatal hypoxia is still important cause of brain damage, and the management of hypoxic baby includes careful maintenance of glycaemia and other homeostatic parameters.